Formal model of semantic search in the electronic library - Дударь, Зоя Владимировна; Белоконь, Василий Анатольевич; Хильский, Виктор Григорьевич (Eastern-European Journal of Enterprise Technologies, 2011)
This article presents a formal model of semantic search in a specialized electronic library. A scheme for constructing an ontology is presented. The lemmas for the functions of interpretation of terms and concepts are formed